Age-Related Performance on Vowel Identification and the Spectral-temporally Modulated Ripple Test in Children With Normal Hearing and With Cochlear Implants. (April 2018) - DiNino, Mishaela; Arenberg, Julie G.
Children's performance on psychoacoustic tasks improves with age, but inadequate auditory input may delay this maturation. Cochlear implant (CI) users receive a degraded auditory signal with reduced frequency resolution compared with normal, acoustic hearing; thus, immature auditory abilities may contribute to the variation among pediatric CI users' speech recognition scores. This study investigated relationships between age-related variables, spectral resolution, and vowel identification scores in prelingually deafened, early-implanted children with CIs compared with normal hearing (NH) children. All participants performed vowel identification and the Spectral-temporally Modulated Ripple Test (SMRT). Vowel stimuli for NH children were vocoded to simulate the reduced spectral resolution of CI hearing. Age positively predicted NH children's vocoded vowel identification scores, but time with the CI was a stronger predictor of vowel recognition and SMRT performance of children with CIs. For both groups, SMRT thresholds were related to vowel identification performance, analogous to previous findings in adults. Sequential information analysis of vowel feature perception indicated greater transmission of duration-related information compared with formant features in both groups of children. In addition, the amount of F2 information transmitted predicted SMRT thresholds in children with NH and with CIs. Comparisons between the two CIs of bilaterally implanted children revealed disparate task performance levels and information transmission values within the same child. These findings indicate that adequate auditory experience contributes to auditory perceptual abilities of pediatric CI users. Further, factors related to individual CIs may be more relevant to psychoacoustic task performance than are the overall capabilities of the child.